Peranan kelompok peternak sapi potong Satwa Mulya terhadap keberdayaan rumah tangga peternak di Desa Brajan, Kecamatan Mojosongo, Kabupaten Boyolali Jawa Tengah - Abdul Lathif Apriyanto; Irdaf Irdaf; Anie Eka Kusumastuti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The purpose of this research were to describe: (1) the implementation of farmers group’s activities in increasing the production of beef cattle, (2) the success of farmers group’s activities in increasing the production of beef cattle and, (3) the success of the farmers group’s role in empowering the farmers. The method of this research was a descriptive with qualitative model. The subject was officers of Satwa Mulya and citizen of Brajan Village. The research data were collected by using the method of participation and observation, interview, and documentation. The researcher wasthe main instrument which assisted with guidelines for observation, interview, and documentation.Method in this research were used data display, data reduction, and conclusion drawing.The results showed that: (1) The existence of farmers groups can increase the farmers knowledge in managing the beef cattle business started from seed selection, feeding, maintenance and marketing. In addition, also be increased the motivation and solidarity of farmers within the group. (2) While the implementation of farmers group’s activities in increasing the beef cattle production is good enough which includes: awarding the concentrates weighing livestock from government, artificial insemination, supplementation and pregnancy checking. (3) Furthermore the success of the farmers group’s role in communitiesproductivity can be seen from the increasing prosperity of farmers in Brajan village.So, it can be concluded that existence of farmers group’s can increase the knowlegde of farmers especially about beef cattle production, their motivation and unity or farmers in its group. Keywords: farmers group, productivity, beef cattle